Exploration of a new tool for assessing emotional inferencing after traumatic brain injury. (7th May 2015) - Zupan, Barbra; Neumann, Dawn; Babbage, Duncan R.; Willer, Barry
Abstract: Objective : To explore validity of an assessment tool under development—the Emotional Inferencing from Stories Test (EIST). This measure is being designed to assess the ability of people with traumatic brain injury (TBI) to make inferences about the emotional state of others solely from contextual cues. Methods and procedures : Study 1: 25 stories were presented to 40 healthy young adults. From this data, two versions of the EIST (EIST-1; EIST-2) were created. Study 2: Each version was administered to a group of participants with moderate-to-severe TBI—EIST 1 group: 77 participants; EIST-2 group: 126 participants. Participants also completed a facial affect recognition (DANVA2-AF) test. Participants with facial affect recognition impairment returned 2 weeks later and were re-administered both tests. Main outcomes : Participants with TBI scored significantly lower than the healthy group mean for EIST-1, F (1, 114) = 68.49, p < 0.001, and EIST-2, F (1, 163) = 177.39, p < 0.001. EIST scores in the EIST-2 group were significantly lower than the EIST-1 group, t = 4.47, p < 0.001. DANVA2-AF scores significantly correlated with EIST scores, EIST-1: r = 0.50, p < 0.001; EIST-2: r = 0.31, p < 0.001. Test–re-test reliability scores for the EIST were adequate. Conclusions : Both versions of the EIST were found to be sensitive to deficits in emotional inferencing. After further development, the EIST may provide clinicians valuable information for intervention planning.